Redescription of earthworm species Tonoscolex monorchis (Stephenson, 1916) (Clitellata: Megascolecidae) from Darjeeling, India—A significant contribution after a quarter of a century - Hasan, Md. Nurul; Reynolds, John Warren; Ahmed, Shakoor; Ghosh, Shyamasree; Mandal, Chandra Kanta; Kosygin, Laishram (Zootaxa, 2026)
The species Tonoscolex monorchis (Stephenson, 1916) was originally described from a single immature specimen collected from Darjeeling district, West Bengal, India. It remains a subject of discussion due to its metandric condition (testes present only in segment 9) and the presence of three pairs of seminal vesicles in segments 10, 11, and 12. Since the original description, one more record was documented with a brief description and without any significant contribution to the taxonomy of the species (Halder, 1999a). In this study, the species is redescribed and illustrated based on fresh collections from Tamsing forest, Darjeeling district, West Bengal, marking a significant contribution to the understanding of the species. Additionally, a brief description and an identification key to the Indian Tonoscolex species are provided to support future research in this field.